2008
DOI: 10.1007/s11033-008-9349-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in chemoattractant receptor expressed on Th2 cells (CRTH2) is associated with asthma susceptibility in Chinese children

Abstract: We investigated the allele and genotype frequencies of two common CRTH2 single nucleotide polymorphisms (SNPs) [G1544C and A1651G (rs 545659)] in the 3'-untranslated region and the relationship between these SNPs and serum IL-13 levels in Chinese children patients with asthma. For G1544C and A1651G SNPs, there were significant differences in allele and genotype frequencies between asthma patients and controls. Haplotype analysis yielded additional evidence of linkage disequilibrium for the 1544G-1651G haplotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…We and others have shown that the CRTh2 single nucleotide polymorphisms (SNPs) rs11571288, rs545659 and rs634681 are associated with asthma and allergic sensitization in ethnically distinct populations . Our previous report also suggested association between CRTh2 rs533116 and allergic asthma, but significance was lost after correcting for multiple comparisons .…”
mentioning
confidence: 85%
“…We and others have shown that the CRTh2 single nucleotide polymorphisms (SNPs) rs11571288, rs545659 and rs634681 are associated with asthma and allergic sensitization in ethnically distinct populations . Our previous report also suggested association between CRTh2 rs533116 and allergic asthma, but significance was lost after correcting for multiple comparisons .…”
mentioning
confidence: 85%
“…CRTH2 also mediates chemotaxis of Th2 lymphocytes, eosinophils and basophils towards PGD2 (7). There is evidence to suggest that genetic alteration of CRTH2 is related to allergic asthma in African‐American (8) and Chinese populations (8–12). There has been no published data addressing the role of the CRTH2 gene in aspirin exacerbated respiratory disease (AERD) pathogenesis.…”
mentioning
confidence: 99%
“…Genetic variations in CRTH2 have been associated with allergic asthma in different ethnic groups 2123. Activation of CRTH2 exacerbates allergic inflammation in an allergic inflammatory mouse model of asthma24, while CRTH2 antagonism ameliorates airway inflammation and hyperreactivity in this model 25, 26.…”
Section: Introductionmentioning
confidence: 99%